Investigation of Body Development in Growing Holstein Heifers With Special Emphasis on Body Fat Development Using Bioelectrical Impedance Analysis - Heine, Kathrin; Kichmann, Viktoria; Kuhlberg, Miriam K. von; Vervuert, Ingrid; Bachmann, Lisa; Lippmann, Jens; Gottschalk, Jutta; Reitemeier, Susanne; Steinhöfel, Ilka; Einspanier, Almuth (Frontiers in Veterinary Science, 2021)
This study analyzed skeletal development, body condition and total body fat development of growing heifers. 144 female primiparous Holstein cattle from four commercial dairy farms with different degrees of stillbirth rates were examined during the rearing period. This included measurements in body condition, fat tissue, metabolic and endocrine factors. Pelvic measurements and the sacrum height were analysed to assess skeletal development. The body condition was classified via body-condition-scoring (BCS), bioelectrical impedance analysis (BIA), back fat thickness (BFT) measurements and the body mass (BM). For the first time, BIA was used as an appropriate method to evaluate the fat tissue content of cattle throughout the rearing period. This analysis technique can be performed on heifers aged 8 to 15 months. Throughout that period the fat content decreased while the skeletal development increased. In addition, high free fatty acids (FFA) concentrations in serum of the animals with high frame development were found, supporting our hypothesis that stored energy of body fat deposits is used for skeletal growth. Furthermore, we were able to demonstrate complex endocrine relationships between fat metabolism and skeletal growth by using specific markers, such as leptin, insulin-growth-factor-1 (IGF-1) and oestradiol (E2). Food analysis showed high crude protein (CP) levels in the total mixed ration above recommendation for daily protein intake of all farms. However, there was a positive correlation between CP and the body frame measurements in our study. In summary, we established a novel regression formula for BIA analysis (“BIA-Heine”) in heifers to evaluate the body composition throughout different ages and physiological stages in the development of heifers. This special formula allows the evaluation of fat tissue without a whole-body analysis and therefore provides an innovative technique for animal welfare support.